2010
DOI: 10.1590/s0102-09352010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carprofen administered by different routes to control experimental uveitis in dogs

Abstract: Efficacy of carprofen, administered by different routes, was studied in experimental uveitis in dogs. Anterior chamber paracenteses was accomplished at two different moments (M0 and M1), with a five hour interval between them. At M0 and M1, 0.2mL of aqueous humor was collected and quantitation of total protein and prostaglandin E 2 (PGE 2 ) were determined. Four groups were formed (n=8), which received carprofen at the end of M0, by the following routes: subcutaneous (GIm), subconjunctival (GII), and topical (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In spite of it, atropine eye drops proved to produce a longer‐lasting effect of 13 h and to promote a more pronounced pupillary dilation (0.9 mm) when compared with the same drug delivered through the subconjunctival route. Studies in dogs demonstrated that subconjunctival route was less efficient in stabilizing blood–aqueous barrier than the topical route after the use of anti‐inflammatory drugs . Considering the average ± SD weight of 35.73 ± 1.23 kg of the individuals used in the study, an injection of 0.4 mL (4 mg/injection) did not exceed the total dose allowed for the species (0.05–0.20 mg/kg) and was chosen based on the veterinary literature and the volume tolerated by this route of administration …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of it, atropine eye drops proved to produce a longer‐lasting effect of 13 h and to promote a more pronounced pupillary dilation (0.9 mm) when compared with the same drug delivered through the subconjunctival route. Studies in dogs demonstrated that subconjunctival route was less efficient in stabilizing blood–aqueous barrier than the topical route after the use of anti‐inflammatory drugs . Considering the average ± SD weight of 35.73 ± 1.23 kg of the individuals used in the study, an injection of 0.4 mL (4 mg/injection) did not exceed the total dose allowed for the species (0.05–0.20 mg/kg) and was chosen based on the veterinary literature and the volume tolerated by this route of administration …”
Section: Discussionmentioning
confidence: 99%
“…Studies in dogs demonstrated that subconjunctival route was less efficient in stabilizing blood-aqueous barrier than the topical route after the use of anti-inflammatory drugs. 23,24 Considering the average AE SD weight of 35.73 AE 1.23 kg of the individuals used in the study, an injection of 0.4 mL (4 mg/injection) did not exceed the total dose allowed for the species (0.05-0.20 mg/kg) 25 and was chosen based on the veterinary literature and the volume tolerated by this route of administration. 26 In Santa Inês sheep, the sympathomimetics phenylephrine and ibopamine did not cause alterations in pupil diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior chamber paracentesis was performed under general anesthesia as previously described (Ribeiro et al 2010, Gilmour et al 2012 and 0.2mL of aqueous humor was slowly aspirated. In patients with cataract, the aqueous humor was collect at the end of the eletroretinographic examination.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying possible chemical mediators involved in the pathogenesis of anterior uveitis and LIU is important because could have direct therapeutic implications, and the knowledge can be used to minimize the potential vision-threatening sequelae that result from intraocular inflammation (Chiou et al 1994, Pinard et al 2011. Aqueous humor concentrations of prostaglandin E 2 (PGE 2 ), tumor necrosis factor-α, cicloxigenase-2, nitric oxide synthase, nitrites, nitrates, MMP-3 and -9 have been studied in dogs subjected to experimental breakdown of the blood-aqueous barrier (Ribeiro et al 2010, Pinard et al 2011, Gilmour et al 2012. Nonetheless, to date, the only cytokines dosed in the aqueous humor of dogs with cataracts were the vascular endothelial growth factor and PGE 2 (Abrams et al 2011, Sandberg et al 2012, Renzo et al 2014.…”
Section: Introductionmentioning
confidence: 99%